Structural optimization of transmission towers using a novel Genetic Algorithm approach with a variable length genome. (1st August 2021) - Khodzhaiev, Marat; Reuter, Uwe
Graphical abstract: Highlights: Optimization of transmission towers requires complex varying of shape and topology. A novel optimization approach of two-stage mutation is developed for handling a variable length genome. The first stage is deterministic varying of topology, i.e. the number of panels. The second stage is random varying of shape, i.e. the heights of the panels. Using the developed approach, the cost of a real-life transmission tower was decreased by 10%. Abstract: This paper presents an approach to topology, shape, and size optimization of transmission towers. The key feature of the presented approach is the independent variation of the number and heights of tower panels. For that purpose, a modified version of a Genetic Algorithm with a variable length genome is utilized. A novel method of two-stage mutation is developed for handling a variable length genome. Structural optimization of a 110 kV transmission tower is performed as a demonstration with the key result of 10% cost reduction.